Laki-Laki sebagai Sekutu Gerakan Feminis: Pelibatan Laki-Laki sebagai Strategi Gerakan Advokasi yang Dilakukan oleh Jaringan Masyarakat Sipil dalam Mendorong Pengesahan Undang-Undang Tindak Pidana Kekerasan Seksual - Nadia; Dirga Adiansa (Yayasan Jurnal Perempuan, 2023)
This research discusses the advocacy strategy carried out by the Civil Society Network (JMS) by involving men to push for the ratification of the TPKS Law. By referring to the theory of the strategic capacity of gender equality policy advocates by Htun and Weldon, JMS has used organizational capacity through strategies of (1) framing demands; (2) building networks, and (3) lobbying policymakers. This study uses a qualitative method by conducting in-depth interviews to obtain primary data and collecting secondary data through a study of documents including regulations, news, and previously existing scientific papers. The findings from this study indicate that JMS involves men in advocacy strategies that are carried out by utilizing the privileges of men. For instance, the involvement of male religious leaders to counter the narrative of rejection of the TPKS Law which considers the TPKS Law to be inconsistent with the religious and moral values of the Indonesian people. Apart from that, JMS also involves male legislators who have a strategic position as Chairperson of the TPKS Law Working Committee to help lobby other members of the Indonesian Parliament.